Analisis Kebangkrutan Model Altman, Springate, Dan Zmijewski Pada Perusahaan PT. Chitose Internasional Tbk Periode 2018-2020 - Retnaning Diah, Selvi (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2025)
PT. Chitose Internasional Tbk is a furniture company, known to experience a setback in 2018-2020. This is due to the policies implemented by the government to prevent the spread of COVID-19, resulting in a severe economic recession. To provide insight into the company's health and financial performance information, bankruptcy analysis is needed as an early warning, the earlier signs of bankruptcy are detected, the better for the company to make improvements. This study aims to determine the financial performance, and to determine the viability of the company PT Chitose Internasional Tbk in 2018-2020. This research was conducted using the bankruptcy analysis method, namely Altman z-score, Springate, and Zmijewski. The object of this research is the company's financial statements PT Chitose Internasional Tbk. The research results of PT Chitose Internasional Tbk using the Altman z-score have the potential to go bankrupt in 2018 and 2020, and in 2019 the company is in the gray zone. By using the springate method has the potential to go bankrupt in 2019 and 2020, while in 2018 the company does not have the potential to go bankrupt. By using the zmijewski method, there is no potential for bankruptcy for 3 years (2018-2020).